2023
DOI: 10.3389/fonc.2023.1133008
|View full text |Cite
|
Sign up to set email alerts
|

MRI-based pre-Radiomics and delta-Radiomics models accurately predict the post-treatment response of rectal adenocarcinoma to neoadjuvant chemoradiotherapy

Abstract: ObjectivesTo develop and validate magnetic resonance imaging (MRI)-based pre-Radiomics and delta-Radiomics models for predicting the treatment response of local advanced rectal cancer (LARC) to neoadjuvant chemoradiotherapy (NCRT).MethodsBetween October 2017 and August 2022, 105 LARC NCRT-naïve patients were enrolled in this study. After careful evaluation, data for 84 patients that met the inclusion criteria were used to develop and validate the NCRT response models. All patients received NCRT, and the post-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 47 publications
(34 reference statements)
1
3
0
Order By: Relevance
“…may have the potential to further enhance the expression of this heterogeneity, contributing to the diagnostic performance ( Jiang et al, 2022a ; Jiang et al, 2022b ). The mRMR, ADASYN, and Bayesian optimization algorithms also showed the excellent selection performance in radiomics analysis, which is consistent with the findings of Xie et al (2021) , Hou et al (2022) , Wang et al (2023) , and Wu et al (2023) .…”
Section: Discussionsupporting
confidence: 81%
“…may have the potential to further enhance the expression of this heterogeneity, contributing to the diagnostic performance ( Jiang et al, 2022a ; Jiang et al, 2022b ). The mRMR, ADASYN, and Bayesian optimization algorithms also showed the excellent selection performance in radiomics analysis, which is consistent with the findings of Xie et al (2021) , Hou et al (2022) , Wang et al (2023) , and Wu et al (2023) .…”
Section: Discussionsupporting
confidence: 81%
“…Another bleak explanation could be that some studies did not apply the resampling correctly. If only cross-validation is used without an independent test set, it is of utmost importance that resampling is applied only to the training set and does not utilize the validation set in any way 20 , 21 . If this is not followed, a large bias can be expected 22 , 23 ; yet, this kind of error is common 24 and often cannot be detected without access to the code, which is most often not provided in radiomic studies.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, SMOTE, bSMOTE, and KMeans SMOTE also demonstrated good performance, which can provide a reference for other imbalanced biomedical data processing. A recent study ( 38 ) reported that machine learning mining results using the SMOTE method were largely consistent with the baseline patterns or trends, and synthetic data generated using machine learning have shown advantages in clinical modeling ( 39 ). XGBoost is a novel tree-based algorithm for sparse data processing that provides the gradient-boosted decision tree, which is widely recognized in data mining challenges and tasks ( 40 , 41 ).…”
Section: Discussionmentioning
confidence: 99%